The Effect of Triphenylbismuth on the Radiopacity and Performance Properties of Compression- and Injection-Molded Denture Resins - Lisa A. Lang, DDS, MS,1 Patrick A. Mattie, DDS, MS,2 and H. Ralph Rawis, PhD3 (Blackwell Synergy, 2000)
Methods of incorporating radiopaque triphenylbismuth into an experimental compression- molded and injection-molded heat-polymerized resins were determined. The transverse flexural properties, radiopacity, and color stability of the resins containing triphenylbismuth were then compared with a commercially available, compression-molded denture resin. Materials and Methods: Varying levels of triphenylbismuth were added to both